Draft Annual Plan 1986-87 Volume VI Power Jammu and Kashmir Government - Planning Commission (Planning Commission, 1985)
Detailed projects are to be framed and cleared. An outlaw A of Rs. 36.40 Crores has been proposed for the 7th Plan for this work. An expenditure of 5.80 Crores is proposed for the year 1986-87. An amount of Rs.100 Lakhs for the annual Plan 1986-87 has been kept in item Sub—Transmission under the Sub-head "Transmission and Distribution" against the provision of Rs.322 Lakhs provided in the 7th Plan 1985-90 vide Addl.
Jammu and Kashmir Government, Planning and Development Department